PRODUCTIVITY AND QUALITY OF WINTER WHEAT DEPENDING ON A FACTOR OF BIOLOGIZATION - N. V. Parakhin; A. F. Melnik (Зерновое хозяйство России, 2018)
Winter wheat plays a leading part in food security of RF. Though winter wheat productivity greatly increased, the share of food wheat in domestic import doesn’t exceed 20%.  As there is a great need of competitive goods on a world market, grain quality increase is a key purpose of agriculture. The major factors promoting high productivity and quality of winter wheat are adaptive technologies based on the principles of agricultural biologization. We carried out the assessment of the factors of biologization, greatly influencing on productivity and harvesting winter wheat grain of high quality. It was shown that present winter wheat varieties possessing a high productive potential largely depend on weather conditions during vegetation. We studied the response of new geno types and selected some adapted winter wheat varieties during growing in arid forestry steppe parts of Central Chernozemie of RF. It was established that a choice of varieties adapted to local conditions gives a stable yield (more than 5,0 t/ha) with a gluten content 24-28% and a protein content 13,2-14,8%. We determined the effect of intended use of clover and ‘Timofeevskaya’ grass mixture on productivity and quality of winter wheat. Plowing of clover and ‘Timofeevskaya’ grass mixture and partial fertilizing increase productivity and quality of winter wheat grain that meet the requirements of the 3-d class of GOST.